جمالية التلقي في كتاب "المحصول في علم الأصول" لفخر الدين الرازي (ت606هـ/1210م) - بثينة الجلاصي (International Institute of Islamic Thought, 2017)
تنوعت اهتمامات الأصوليين في مصنفاتهم التأصيلية؛ إذ لم يقتصروا على تعريف الأدلة وإثبات حُجيتها وعرض مسائل الخلاف فيها، وإنَّما دقَّقوا في المسائل اللغوية، وتحدَّثوا في تفاصيل لم يتحدَّث فيها اللغويون أنفسهم، وفصَّلوا القول في قضايا بلاغية، من بينها قضية التلقي وجماليته. ولقد كان فخر الدين الرازي من الذين أضافوا إلى مبحث التلقي وأثره في المخاطب، فتحدَّث في كتابه "المحصول في علم الأصول"، في باب الحقيقة والمجاز، عن مراحل التلقي، ومظاهر جماليته، وشروط تأثيره. ولئن استفاد الفخر من الدرس البلاغي، وممَّن سبقوه، فإنَّه أضاف الكثير من المفاهيم التي نجدها عند القزويني في "الإيضاح"، مثل: أفق الانتظار، والشوق، والدغدغة النفسانية. The interests of Usuli Scholars have varied in their Usuli works; they did not limit themselves to defining the evidence, proving its validity and presenting the issues of disagreement, they also investigated the linguistic issues, discussed areas that were not covered by the linguists, and provided the arguments in rhetorical issues, including the issue of reception and its aesthetics. Al-Razi was one of those who added to the subject of reception and its impact on the addressee. In the chapter of "Reality and Metaphor," he wrote about the stages of receiving, the manifestations of aesthetics, and the conditions of its influence. Although he benefited from rhetoric and from his predecessors, he also added many of the concepts that we find in al-Qazwini's Book Idah, such as the horizon of waiting, longing, and psychic tickling.